Yeni Dijital Çağda Toplumsal Hareketlerde Meydana Gelen Dönüşüm - Çaycı, Berk (The Turkish Online Journal of Design Art and Communication, 2015)
Transformations at technological economical, political, social and cultural fields within historical process has been effecting all units of society. Herewith, transformation which occurs in field of human activity, generates changeovers on societies’ shape of understanding and interpretation the world. At the core of this change, new media which includes new digital communication medias like increasing individual mobility and social networking webs with generic definiton is located as well as economical, political, social, ideological and cultural factors. As a consequence of these; traditional movements have been giving place to new non-rigid decentralised global movements that universal values are supported with the process of passing to post-industrial era. Within new era, owing to internet converges to mobil communication technologies, individuals who are organised with the networks, can come together within the scope of universal topics like notably “quality of life”, “human rights”, “terrorism threat” and enviromental movements, internet freedom, violence to women, democratic participation and freedom. With this study, transformation in social movements through historical process will be presented within the scope of an argumantative work with economical, social, cultural and technological dimensions- notably globalization- and it will be chronogically in order.
Keywords: Yeni Toplumsal Hareketler; Ağlarda Örgütlenen Toplumsal Hareketler; Küreselleşme; Mobil İletişim Teknolojileri; New Social Movements; social Movements Which are Organized in Networks; Globalization; Mobil Communication Technologies